2022
DOI: 10.2113/2022/3086647
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High-Temperature Treatment on Strength and Failure Behaviors of a Quartz-Rich Sandstone under True Triaxial Condition

Abstract: In this paper, the effect of high temperature on the mechanical properties of quartz-rich sandstone was studied by true triaxial pressure experiment. The density, P-wave velocity, elastic modulus, peak stress, peak strain, and failure mode of quartz-rich sandstone before and after heat treatment were analyzed and compared. It was found that the color of quartz-rich sandstone changes greatly when heated to 500°C. In detail, the brittleness of quartz-rich sandstone gradually decreased and the ductility increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…By studying the failure pattern of rocks under different high temperatures it can be found that the failure was transformed from brittleness to ductile brittleness, and the failure degree intensified with the increase of temperature. Li et al 34 – 36 explored the fragmentation characteristics of the coal–rock-like combined body under impact load and concluded that the combinations mostly showed splitting failure, and the failure surface was relatively flat. Some studies 37 – 40 have found that the coal body was damaged first when the coal–rock combined body was destroyed under compressive load, and the expansion of cracks might lead to the failure of the rock body.…”
Section: Introductionmentioning
confidence: 99%
“…By studying the failure pattern of rocks under different high temperatures it can be found that the failure was transformed from brittleness to ductile brittleness, and the failure degree intensified with the increase of temperature. Li et al 34 – 36 explored the fragmentation characteristics of the coal–rock-like combined body under impact load and concluded that the combinations mostly showed splitting failure, and the failure surface was relatively flat. Some studies 37 – 40 have found that the coal body was damaged first when the coal–rock combined body was destroyed under compressive load, and the expansion of cracks might lead to the failure of the rock body.…”
Section: Introductionmentioning
confidence: 99%
“…As the slag particles have a certain cohesion compared with ordinary rocks, the difference in material characteristics affects the mechanical properties of TSM. Most of the physical and mechanical properties of the SRM have been studied in three ways: laboratory testing, numerical simulation, and theoretical analysis (Chen et al, 2021;Li et al, 2022). Xing et al (2020) used particle flow software to simulate the triaxial test numerically and elucidated the micro-mechanism of SRM with different rock content.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars determined the shear behaviors of structural planes by using numerical simulations. Based on the characteristics of discontinuity, heterogeneity and anisotropy of rock structure [ 21 , 22 , 23 ], it is most suitable to choose particle follow code method (PFC) to conduct numerical simulations [ 24 , 25 ]. PFC can conduct research on the mechanical characteristics of a rock structure from the micro level and simulate the mechanical behavior of rock in different working situations, which can provide a supplement to and comparison with laboratory testing [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%